Distribution, scaling, and depiction of the temporal branches of the facial nerve - Bradley R. Hunt; Santos A. Johson; Zachary S. Klukkert (Scientific Reports)
Abstract Iatrogenic injury to the temporal branches of the facial nerve (CN VII) is the leading postoperative complication of the preauricular surgical approach to the temporomandibular joint (TMJ). Many of the anatomical illustrations vary greatly in how the anatomy of the temporal branches of the facial nerve are depicted. Additionally, there are few studies that discuss this variation. This study aims to provide more accurate data on this discrepancy. Here, the distribution of temporal branches of the facial nerve was examined in 20 cadaveric donors. A count of branches and the location of each was mapped as they crossed the zygomatic arch, with attention paid to variation in the breadth of the nerve free “preauricular window” which is pertinent to the surgical access to the TMJ. Comparable measures were collected from published anatomical illustrations and tested for accuracy. Preauricular window breadth measurements were found to be comparable to previous studies, but the mean value was lower here. Patterns in the nerve distribution fit a proportional model whereby the zygomatic length (ZL) is divided into five equal segments, the most posterior of which was found to be free of CN VII branches in all donors. In anatomic illustrations, the number of nerve branches crossing ZL was undercounted and the breadth of the preauricular window was overestimated. Results suggest that controlling for face size could reduce the variation observed in the breadth of the facial nerve-free zone near the TMJ. Non-cadaveric reference illustrations do not represent the anatomy accurately.